Development of method for operation support of the cogeneration systems on biogas fuel - Чайковська, Євгенія Євстафіївна; Стефанюк, Вадим Володимирович (Technology audit and production reserves, 2015)
It is developed a method of maintaining the temperature of the local water temperature during measurement of return water temperature and heater coolant temperature in the inlet and outlet of the engine cooling circuit from the heat exchanger on the basis of the proposed cogeneration system. Decisions on changing the number of plates of the heat exchanger while maintaining a constant coolant flow rate allows to coordinate the discharge-charge of the biogas plant, unloading of the fermented wort, loading of the fresh material and charge-discharge of a cogeneration system using a heat pump for which fermented wort is low-grade energy source. For example, when using the proposed method of coordination of production and energy consumption in the cogeneration plant, for example, GTK 35 M type with a primary capacity 112 kW, which consumes 352,5 m3/day of biogas, it is possible to obtain biogas savings – 25,4 thousand m3/year that by increasing the marketability of the biogas plant to 13,94 % makes it possible to reduce the cost of production of electric energy and heat up to 20-30 %. Annual energy savings in terms of fuel equivalent is 19,5 tons, and the cash equivalent of additional produced energy is about 100000 UAH/year.